"PBL on 'roids" : application of an adapted constructivist learning environment survey to investigate the perceptions of students in a community-based undergraduate obstetrics learning placement - Marcus, J. K. (Jason Kirk) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhill)--University of Stellenbosch, 2011.